Box–Behnken study design for optimization of bicalutamide-loaded nanostructured lipid carrier: stability assessment. (August 2015) - Kudarha, Ritu; Dhas, Namdev L.; Pandey, Abhijeet; Belgamwar, Veena S.; Ige, Pradum P.
Abstract Bicalutamide (BCM) is an anti-androgen drug used to treat prostate cancer. In this study, nanostructured lipid carriers (NLCs) were chosen as a carrier for delivery of BCM using Box–Behnken (BB) design for optimizing various quality attributes such as particle size and entrapment efficiency which is very critical for efficient drug delivery and high therapeutic efficacy. Stability of formulated NLCs was assessed with respect to storage stability, pH stability, hemolysis, protein stability, serum protein stability and accelerated stability. Hot high-pressure homogenizer was utilized for formulation of BCM-loaded NLCs. In BB response surface methodology, total lipid, % liquid lipid and % soya lecithin was selected as independent variable and particle size and %EE as dependent variables. Scanning electron microscopy (SEM) was done for morphological study of NLCs. Differential scanning calorimeter and X-ray diffraction study were used to study crystalline and amorphous behavior. Analysis of design space showed that process was robust with the particle size less than 200 nm and EE up to 78%. Results of stability studies showed stability of carrier in various storage conditions and in different pH condition. From all the above study, it can be concluded that NLCs may be suitable carrier for the delivery of BCM with respect to stability and quality attributes.